Aseptic meningitis outbreak associated with echovirus 4 in Northern Europe in 2013-2014 - Smura, Teemu; Blomqvist, Soile; Kolehmainen, Pekka; Schuffenecker, Isabelle; Lina, Bruno; Boettcher, Sindy; Diedrich, Sabine; Love, Arthur; Brytting, Mia; Hauzenberger, Elenor; Dudman, Susanne; Ivanova, Olga; et al. (Journal of Clinical Virology, 2021)
Picornaviruses (family Picornaviridae) are small, nonenveloped, positive-sense, single-stranded RNA viruses. The members of this family are currently classified into 47 genera and 110 species. Of picornaviruses, entero-and parechoviruses are associated with aseptic meningitis. They are transmitted via fecal-oral and respiratory routes, and occasionally, these viruses may cause a brief viremia and gain access to central nervous system (CNS). During the diagnostic screening of entero-and parechovirus types in Finland in year 2013-14, we detected a cluster of echovirus 4 (E4) infections in young adults and adolescents. As E4 is infrequently detected in Finland, we contacted several Northern and Central European laboratories that conduct routine surveillance for enteroviruses and, for those who have had E4 cases, we send a query for E4 sequences and data. Here we report CNS infections caused by E4 in Finland, Sweden, Norway, Denmark, Iceland and Germany in 2013 and 2014, and show that the E4 detected in these countries form a single lineage. In contrast, E4 strains circulating in these countries preceding the year 2013, and those circulating elsewhere in Europe during 2013-2014, formed several independent clusters. Peer reviewed